Macrosystems ecology: A new engine and frontier in contemporary ecosystem science - Guirui Yu; Zongxu Yu; Zhi Chen; Qiufeng Wang (Geography and Sustainability, 2025)
Ecosystems are complex systems shaped by both self-organization and anthropogenic regulation, emerging from the dynamic interplay among water, land, climate, biota, and human activities. As the foundational habitat for human well-being, they provide essential services including ecological goods, natural resources, cultural value, and livable environments. Amid accelerating global change, intensifying environmental pressures, and deepening disciplinary integration, ecosystem science is entering a period of transformative development. This study identifies macrosystems ecology, grounded in the principles of large-scale ecological processes, as a pivotal framework for driving the future of ecosystem science. We propose an integrated theoretical, epistemological, engineering and technological system to support this evolution, and retrospectively examine the origins and scientific mission of macrosystems ecology. Core questions, practical applications, research subjects, paradigms, and methodological systems are systematically outlined. In addition, we articulate the multidisciplinary principles, epistemological framework, and axiomatic system that underpin a coherent structure for macrosystems ecology. Together, these components offer strategic guidance for advancing both theoretical understanding and practical innovation in sustainable ecosystem management.